2015
DOI: 10.1128/jcm.03385-14
|View full text |Cite
|
Sign up to set email alerts
|

Application of Whole-Genome Sequencing for Bacterial Strain Typing in Molecular Epidemiology

Abstract: Nosocomial infections pose a significant threat to patient health; however, the gold standard laboratory method for determining bacterial relatedness (pulsed-field gel electrophoresis [PFGE]) remains essentially unchanged 20 years after its introduction. Here, we explored bacterial whole-genome sequencing (WGS) as an alternative approach for molecular strain typing. We compared WGS to PFGE for investigating presumptive outbreaks involving three important pathogens: vancomycin-resistant Enterococcus faecium (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
199
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(211 citation statements)
references
References 57 publications
11
199
0
1
Order By: Relevance
“…In this regard, WGS was superior to PFGE due to its enhanced discriminatory power (Table 2) (0.997 versus 0.892), which has been noted in other studies of bacterial outbreaks (31,79,99,100). In particular, our results are similar to those of Salipante and colleagues (79), who used a different approach to identify SNPs and define outbreak strains but arrived at the same conclusions regarding the deficiencies of PFGE in the context of an A. baumannii outbreak. At the molecular level, this reflects the relatively large number of SNPs that can accumulate in genomes before they are detectable by PFGE (79).…”
Section: Figsupporting
confidence: 80%
See 2 more Smart Citations
“…In this regard, WGS was superior to PFGE due to its enhanced discriminatory power (Table 2) (0.997 versus 0.892), which has been noted in other studies of bacterial outbreaks (31,79,99,100). In particular, our results are similar to those of Salipante and colleagues (79), who used a different approach to identify SNPs and define outbreak strains but arrived at the same conclusions regarding the deficiencies of PFGE in the context of an A. baumannii outbreak. At the molecular level, this reflects the relatively large number of SNPs that can accumulate in genomes before they are detectable by PFGE (79).…”
Section: Figsupporting
confidence: 80%
“…In particular, our results are similar to those of Salipante and colleagues (79), who used a different approach to identify SNPs and define outbreak strains but arrived at the same conclusions regarding the deficiencies of PFGE in the context of an A. baumannii outbreak. At the molecular level, this reflects the relatively large number of SNPs that can accumulate in genomes before they are detectable by PFGE (79). In addition, our study found three variants of the same strain within a single pa-…”
Section: Figsupporting
confidence: 79%
See 1 more Smart Citation
“…[7][8][9] Acinetobacter baumannii is resistant to desiccation and to disinfectants, it is difficult to be treated and to be eradicated and it requires rigorous monitoring programs to prevent and control hospital outbreaks. [10] Guidance documents [11][12][13] on the control of Acinetobacter baumannii nosocomial infections are based on the combined interventions including an active microbiological surveillance, precautions to contain the spread of infections from patient to patient and nursing care protocols for colonized patients. Additional measures regard: antibiotic use restriction, careful hand hygiene, extensive environmental surface decontamination procedures [14] and clinical staff education on how to deal with an outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the resolution of standard typing methods and the frequent absence of environmental samples often make it difficult to conclusively link cases or identify environmental reservoirs. The use of whole-genome sequencing (WGS) to compare entire bacterial genomes at the single nucleotide level can, however, greatly improve clustering of bacterial pathogens (39).…”
mentioning
confidence: 99%